1962
DOI: 10.1086/267126
|View full text |Cite
|
Sign up to set email alerts
|

Party Government and the Saliency of Congress

Abstract: NY mid-term congressional election raises pointed questions I \ about party government in America. With the personality of y m \ the President removed from the ballot by at least a coat-JL A_tail, the public is free to pass judgment on the legislative record of the parties. So the civics texts would have us believe. In fact, however, an off-year election can be regarded as an assessment of the parties' record in Congress only if the electorate possesses certain minimal information about what that record is. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0
3

Year Published

1971
1971
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(90 citation statements)
references
References 0 publications
3
84
0
3
Order By: Relevance
“…Certain authors (e. g. Stokes and Miller 1962, Cummings 1966, Erikson 1971 noticed that there is a certain advantage possessed by incumbent politicians compared to their challengers in elections to both houses of the U. S. Parliament. The most frequent explanation of IA is based on the higher quality of defenders than challengers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain authors (e. g. Stokes and Miller 1962, Cummings 1966, Erikson 1971 noticed that there is a certain advantage possessed by incumbent politicians compared to their challengers in elections to both houses of the U. S. Parliament. The most frequent explanation of IA is based on the higher quality of defenders than challengers.…”
Section: Discussionmentioning
confidence: 99%
“…Různí autoři (Stokes a Miller 1962, Cummings 1966: 68-75, Erikson 1971) si začali všímat toho, že ve volbách do obou komor amerického parlamentu existuje určitá výhoda, kterou mají stávající poslanci či senátoři oproti kandidátům, kteří se o mandát ucházejí jako jejich vyzyvatelé. 5 Tato problematika se poté stala jedním z vůbec nejčastějších témat výzkumů amerických politologů a sociologů zabývajících se volebním chováním, nicméně kromě čistě empirických studií se autoři zaměřili zejména na dvě subtémata.…”
Section: Koncept Incumbency Advantageunclassified
“…The electorate indeed often lacks interest to be informed about the incumbents' voting records and relies mainly on party identity, therefore voters cannot hold their representatives accountable (Stokes and Miller 1962). In any event, Ansolabehere and Jones (2010) show for the United States that voters have preferences over important bills and use their beliefs about legislators' roll-call votes and parties' policy orientation to vote for their representatives.…”
Section: Introductionmentioning
confidence: 99%
“…In such elections, it is reasonable to expect that a substantial portion of the electorate is unfamiliar with the candidates, given that research 5 has shown that even in congressional elections in the US about a third to half of the electorate is not able to recall or does not even recognize the name of the candidates (e.g. Stokes and Miller 1962, Goldenberg and Traugott 1980, Mann and Wolfinger 1980. A particular strength of our research design is that we are thus able to test the causal impact of messages employing partisan cues on turnout in a real-world…”
mentioning
confidence: 99%
“…Significant proportions of the electorate are not able to recall, or do not even recognize, the name of candidates running in congressional elections in the US, in particular if the candidate is not an incumbent (e.g. Stokes and Miller 1962, Goldenberg and Traugott 1980, Mann and Wolfinger 1980. Similarly, it is highly likely that many voters in the UK and elsewhere are not familiar The contribution of this paper to understanding the role of partisan cues in campaign appeals is important not only because it allowed us to gain insight into the particulars of voter decision-making in real-world campaign environments, but also because it has serious consequences for the conduct of 26 partisan election campaigns.…”
mentioning
confidence: 99%